Mining Github for Factors That Affect Open Source Software Sustainability - Alshomali, Mohammad Azees Abdulhassan; Albayati, Wurood (International Journal of Membrane Science and Technology, 2023)
Open-Source Software (OSS) is everywhere. The availability of such software enables researchers in software engineering to have a deep insight into the factors that affect the success of the software. Some OSS repos get more popular and evolve over time, while others may only survive for a couple of months. This study aims to help developers identify internal factors that affect the sustainability of their software. Firstly, identify the most demanding application domain; secondly, observe the most popular repositories (for the demanded application domain) for about three years to identify the factors that help such repos to survive (sustainability factors). Dara mining algorithms (classification and regression) are used as a tool to find the GitHub factors that affect the sustainability of OSS.